The Influence of Personality Domains and Working Experience in Peruvian Managers’ Leadership Styles: An Initial Study - D'Alessio, Fernando (Pontificia Universidad Católica del Perú. CENTRUM, 2008)
The purpose of this quantitative investigation is to examine the relationships that may exist among the five personality domains, working experience, and the three leadership styles in a sample of 500 managerial Master of Business Administration (MBA) students of a leading business school in Peru. Similar studies have previously been performed in developed countries; well-known examples come from the United States of America, Norway, Germany, Australia, Canada, and Singapore, but no such studies are found in a developing country. The Neuroticism Extraversion Openness to Experience Personality Inventory Revised (NEO-PI-R) and Multifactor Leadership Questionnaire (MLQ) were the instruments used for personality and leadership, respectively. In this sample, conscientiousness demonstrates the strongest and most consistent correlation with transformational (.426 ), transactional (.43 0), and passive-avoidant (-.354 ) leadership styles. Extraversion has the next highest correlation with transformational (.400) leadership styles and a weak correlation with transactional (.152) and passive-avoidant (-.166) leadership styles. Agreeableness has no significant correlation with any of the leadership styles, and openness to experience shows a significant correlation only to transformational (.201) leadership styles. Neuroticism shows weak correlations with transformational (-.214 ) and passive-avoidant (.26 7) leadership styles. Conscientiousness and extraversion may encourage individuals to emerge as leaders. Transformational and transactional leadership behaviors are demonstrated more frequently with increasing working experience.
Keywords: Leadership; Leadership Styles; Personality; Personality Domains; Working Experience; https://purl.org/pe-repo/ocde/ford#5.02.04